Cross-Border E-Commerce Trade Index between China and RCEP Countries - Lili, Zhang (Zhang Lili, 2025)
This doctoral thesis investigates the development levels and trade potential of Cross-Border E-Commerce (CBEC) between China and its Regional Comprehensive Economic Partnership (RCEP) partners from 2013 to 2022. Utilizing Principal Component Analysis (PCA), the study identifies key components influencing CBEC development and formulates a scoring method to evaluate these levels among RCEP countries. China consistently leads in CBEC development due to advanced logistics, robust infrastructure, and efficient customs procedures, while Laos lags behind due to significant disparities in infrastructure and economic development. Building on this foundation, the study employs an extended gravity model and system Generalized Method of Moments (GMM) regression to assess the import, export, and total trade potentials between China and RCEP countries. The results reveal that China's CBEC development significantly boosts import volumes, but this positive impact can be moderated or even reversed in economies with a high Digital Economy Development Index. The import trade potential analysis classifies Singapore as having reconstructive potential, suggesting the need to explore new growth strategies such as cross-border live streaming. Meanwhile, Indonesia, Malaysia, the Philippines, and Vietnam show substantial under-trade potential, indicating significant room for growth. For export trade, the study finds that China's CBEC development negatively affects export volumes, suggesting that despite optimizing export structures in certain contexts, overall CBEC development has not markedly increased export volumes. Conversely, CBEC development in RCEP partner countries positively influences export volumes, especially in regions with high internet penetration and developed electronic payment systems. Furthermore, China's per capita GDP positively impacts export volumes, reinforcing the role of domestic market demand and production capabilities in boosting CBEC export supply. Notably, countries like Laos, Indonesia, Japan, South Korea, and the Philippines exhibit insufficient CBEC export trade, indicating untapped export potential. In terms of total trade volumes, the study finds that CBEC development in RCEP partner countries significantly promotes overall trade growth, particularly in economically advanced regions. While China's per capita GDP positively affects total trade volumes by reducing barriers and costs, its CBEC development has shown limited sustained impact on total trade volumes, potentially even exerting negative effects. The study underscores the significant CBEC trade potential between China, Japan, and South Korea, suggesting that enhancing logistics efficiency and improving consumer experiences could unlock further cooperation potential. Additionally, countries like Australia, New Zealand, and Laos need to improve logistics and infrastructure, with support from initiatives like the Belt and Road Initiative, to enhance their CBEC trade capabilities. These insights provide a comprehensive understanding of CBEC trade potential within the RCEP framework and offer strategic guidance for policymakers and businesses to foster sustainable economic growth through enhanced regional cooperation.